A polyimide anode with high capacity and superior cyclability for aqueous Na-ion batteries1. Issue 24 (25th March 2015) - Deng, Wenwen; Shen, Yifei; Qian, Jiangfeng; Yang, Hanxi
<x xml:space="preserve">Abstract</x> A redox-active and water-insoluble polyimide can reversibly bind 2 Na+ ions per molecular unit, demonstrating a high capacity of 130 mA h g−1, a strong rate capability at 10 C rate and excellent capacity retention of 91.2% over 1000 cycles, offering a low cost and environmentally benign anode for aqueous Na-ion batteries.